PENGARUH KOMUNIKASI ORGANISASI, GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN MELALUI KINERJA KARYAWAN SEBAGAI VARIABEL INTERVENING PT WILMAR NABATI INDONESIA GRESIK - jurnalpps pps; Niswan Bayu Syasindy; Indra Prasetyo; Fatimah Riswati (Jurnal Manajerial Bisnis, 2020)
ABSTRACT The purpose of this research is to analyze the influence of organizational communication, leadership style, and organizational culture on employee job satisfaction through employee performance as intervening variable. The sample of this research is employees of PT Wilmar Nabati Indonesia amounted to 150 respondents. Data analysis technique used is analysis with path analysis method with the help of software SPSS version 19. The result of research shows that there is influence between communication variable to employee performance. Leadership style variables have a significant effect on employee performance. organizational culture variables have a significant effect on employee performance. Employee performance variable has a significant effect on job satisfaction. variable Organizational communication has no significant effect on job satisfaction. The leadership style has a significant effect on job satisfaction, and organizational culture has no significant effect on job satisfaction. Keywords: organizational communication, leadership style, organizational culture, employee performance and employee job satisfaction